2017
DOI: 10.1590/s1413-24782017227039
|View full text |Cite
|
Sign up to set email alerts
|

Relações interculturais na vida universitária: experiências de mobilidade internacional de docentes e discentes

Abstract: RESUMOO presente estudo teve como objetivo analisar experiências interculturais de alunos e professores universitários que realizaram programas de mobilidade acadêmica internacional, focalizando os desafios vivenciados, os aspectos facilitadores e os ganhos alcançados. Foram conduzidas 30 entrevistas e o material obtido foi analisado qualitativamente com o auxílio do software Ethnograph. Resultados apontam que os maiores desafios concernem ao processo de adaptação sociocultural, sendo uma das principais dificu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
7
0
10
Order By: Relevance
“…The results related to airfare tickets, rent and food costs can be correlated to a study that evaluated the costs of living in a foreign country and showed that housing represents the main expense (7) . Therefore, the financial factor is one of the main reasons that hinder or impede the experience of international student mobility (12)(13)(14)(17)(18)(19)(20)(25)(26)(27) , and there is a need for future studies regarding this aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results related to airfare tickets, rent and food costs can be correlated to a study that evaluated the costs of living in a foreign country and showed that housing represents the main expense (7) . Therefore, the financial factor is one of the main reasons that hinder or impede the experience of international student mobility (12)(13)(14)(17)(18)(19)(20)(25)(26)(27) , and there is a need for future studies regarding this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The years of 2012 and 2013 had the highest number of exchange programs, which coincides with a high demand for Portuguese-speaking countries in the SwB program (19) . The significant growth of international academic mobility in Brazil in this period occurred due to changes in the direction of governmental public policies related to higher education (20) .…”
Section: Cost Of Livingmentioning
confidence: 99%
“…Some studies about the experience of international students in Brazil sometimes address the topic of friendship, without this being the focus of research. For example, Medeiros, Andrade and Passos have reported experiences of Brazilian students in international mobility and report that the friendship links are among the five most important experiences lived by these students abroad, emphasizing the formation of friendships with exchange students from other countries [38]. Oliveira and Freitas analyzed the experience of Brazilian students abroad and they reported the difficulties of Brazilian students to relate to other students inside and outside the university context and in the formation of friendships and social networks [39].…”
mentioning
confidence: 99%
“…No Brasil, desde a criação das primeiras universidades brasileiras, na década de 1930, as marcas da internacionalização já se faziam presentes com a vinda de professores visitantes ou convidados da Europa e de centros tradicionais, com o objetivo de se instalar ou consolidar o projeto acadêmico das instituições brasileiras emergentes. CONTEL, 2011;FREITAS, 2017) Nota-se que já na criação da primeira universidade criada no Brasil, na década de 1930, a Universidade de São Paulo, instituição criada pela elite política, econômica e intelectual do Estado de São Paulo, desde o seu início esteve voltada para o mundo.…”
Section: (Castro; Cabral Neto 2012)unclassified
“…Essa intenção está caracterizada na formação do seu corpo docente, em parte formado por professores europeus. FREITAS, 2017) Na Europa, a internacionalização da educação superior se constituiu em um processo marcante que seguiu à Segunda Guerra Mundial (1945) para a reconstrução da Europa. Nesse contexto, a internacionalização almejava assistência técnica para o desenvolvimento do continente por meio de acordos científicos, mobilidade estudantil e bolsas de capacitação.…”
Section: (Castro; Cabral Neto 2012)unclassified